SOCIALIZATION PROCESS AFTER RETIREMENT: PERCEPTION of RETIRED PEOPLE on “MEETING DAYS” in SAFRANBOLU PATTERN - Adem SAĞIR (Fırat University, 2019)
The retirement that is generally corresponding to life period of people in old-ages is seen as a process of expansion of the free time and of making sense of social changes which is became evident by the loss of social role. The loss of social role is important for retired person. Because, this missing is caused to look for new socialization areas. One of these socialization areas is “meeting days” such as gold day, money day, evening meetings, meetings for religious purposes, coffee day. When the person gets out his/her loss of role, s/he provides interaction with new social environment and takes an advantage getting money and finds time to fun. Thus, retirees defining new roles for themselves in socialization, also re-define their own identity beyond free-time activities. İn this context, the study has been practiced with the participation in retirees meeting days which carry various purposes, in Karabük/Safranbolu. It has been preferred meeting days of women on this work. Two in-house, four out-home and after all six meeting days activities were observed. These meeting days, between 1 January 2013 and 15 March 2013 have been followed and participated in meeting days which confirmed the date before. In the study, participant observation technic has been used. It is determined activities which doing in meeting days, and analyzed identification of in